Health sequelae of human cryptosporidiosis in industrialised countries: a systematic review - Bethan L. Carter; Rachel M. Chalmers; Angharad P. Davies (Parasites & Vectors, 2020)
Abstract Background Cryptosporidium is a protozoan parasite which is a common cause of gastroenteritis worldwide. In developing countries, it is one of the most important causes of moderate to severe diarrhoea in young children; in industrialised countries it is a cause of outbreaks of gastroenteritis associated with drinking water, swimming pools and other environmental sources and a particular concern in certain immunocompromised patient groups, where it can cause severe disease. However, over recent years, longer-term sequelae of infection have been recognised and a number of studies have been published on this topic. The purpose of this systematic review was to examine the literature in order to better understand the medium- to long-term impact of cryptosporidiosis. Methods This was a systematic review of studies in PubMed, ProQuest and Web of Science databases, with no limitations on publication year or language. Studies from any country were included in qualitative synthesis, but only those in industrialised countries were included in quantitative analysis. Results Fifteen studies were identified for qualitative analysis which included 3670 Cryptosporidium cases; eight studies conducted in Europe between 2004–2019 were suitable for quantitative analysis, including five case-control studies. The most common reported long-term sequelae were diarrhoea (25%), abdominal pain (25%), nausea (24%), fatigue (24%) and headache (21%). Overall, long-term sequelae were more prevalent following infection with Cryptosporidium hominis, with only weight loss and blood in stool being more prevalent following infection with Cryptosporidium parvum. Analysis of the case-control studies found that individuals were 6 times more likely to report chronic diarrhoea and weight loss up to 28 months after a Cryptosporidium infection than were controls. Long-term abdominal pain, loss of appetite, fatigue, vomiting, joint pain, headache and eye pain were also between 2–3 times more likely following a Cryptosporidium infection. Conclusions This is the first systematic review of the long-term sequelae of cryptosporidiosis. A better understanding of long-term outcomes of cryptosporidiosis is valuable to inform the expectations of clinicians and their patients, and public health policy-makers regarding the control and prevention of this infection. Systematic review registration PROSPERO Registration number CRD42019141311